Prediction of post-traumatic growth based on psychological well-being and mindfulness during Coronavirus conditions among female nurses - Afzali, Maryam; Hajizadeh koli, Shabnam; Aber, Parand; Ghasemi, Narjes (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the role of psychological well-being and mindfulness in predicting post-traumatic growth among female nurses during Coronavirus conditions. Methods: The present study is descriptive and correlational, and the statistical population included female nurses living in Shahriar city who experienced working in hospitals during Coronavirus conditions. In this study, 211 people were selected by the convenience sampling method among the statistical population. The Tedeschi and Calvin (1996) Injury Growth Inventory, the Ryff's Psychological Well-Being Scale (2002), and the Brown and Ryan Mindful Attention Scale (2003) were used to evaluate the participants of the study. The data were analyzed using the simultaneous multiple regression by SPSS software version 23. Results: The results indicate that psychological well-being and mindfulness can predict post-traumatic growth among female nurses (P = 0.01). Also, there is a direct relationship between psychological well-being and post-traumatic growth and mindfulness and post-traumatic growth among female nurses (α = 0.05, P = 0.001). Conclusion: It is recommended to use techniques to increase psychological well-being and mindfulness among female nurses to help promote post-traumatic growth among them.